Fast Track Arbitration in Construction Industry: A Systematic Literature Review Identifying the Key Factors and Challenges for Current Trends - Khodijah Muhd Fadhlullah Ng, Nur; Ismail, Zulhabri; Hashim, Norfashiha; Mat Nasir, Nasyairi (International Journal of Engineering and Technology, 2018)
In the construction industry, differences in perceptions may exist among project participants, therefore, conflicts are inevitable and can quickly turn into disputes. It can be resolved or settled through litigation and Alternative Dispute Resolution (ADR). Arbitration is the most established and well sought-after method. Even so, the arbitral process takes a long time which leads to the fast track arbitration approach. It is expected that the fast track arbitration approach can minimise the time and optimise the cost. However, to date, there is limited established data on the application of fast track arbitration. The present review is trying to compiled the key factors and challenges of fast track arbitration over the last eight years within the construction industry, from August 2010 to April 2018. The systematic review was limited to eight indicators: i) willingness of parties, ii) delay in proceeding, iii) cost controls, iv) time consuming, v) knowledge and awareness, vi) arbitral tribunal reputation, vii) expertise in arbitration, and viii) clear guideline. Literature searches were conducted using predefined keywords in six major databases, including Hein Online, Elsevier, Web of Science, Lexis Nexis, ASCE, and ProQuest. The abstracts and full-text articles of potentially relevant papers were screened to determine the eligibility. Data was abstracted for 36 eligible articles. The review primarily attempted to seek answers to the following two questions: (1) What are the different research approaches used to study fast track arbitration? (2) What is the status of recent publications on fast track arbitration? This study addresses the recent publications revealing that while fast track arbitration is evolving, there is still a gap in the application of fast track arbitration on its benefits. Thus, the findings may act as a catalyst for conducting further research in this field of study. Â